Anemia and health-related quality of life in South Korea: data from the Korean national health and nutrition examination survey 2008–2016 - Kim, Young-Ju (BMC Public Health, 2019)
BACKGROUND: Anemia is associated with impaired quality of life (QoL). We examined the relationship between anemia and QoL in the Korean population using the EuroQol five-dimensional (EQ-5D) questionnaire. METHODS: Data of 30,526 subjects were included from the Korean National Health and Nutrition Examination Survey (2008–2016). The QoL was assessed using three-levels of the EQ-5D questionnaire (G1, G2, and G3). Analysis of variance was used to compare the prevalence of anemia according to the three levels of health status in each of the five dimensions of EQ-5D. Multiple linear regression analysis was used to evaluate the association between hemoglobin level and QoL, and multivariable logistic regression analysis was used to evaluate the odds ratios (ORs) and 95% confidence intervals (CIs) for low levels of each of the five dimensions of EQ-5D. RESULTS: As the level of EQ-5D was worse (from G1 to G3), the prevalence of anemia increased (p for trend < 0.001). Hemoglobin level and EQ-5D showed positive association after adjusting for all covariates such as age, sex, smoking, alcohol drinking, exercise, education, income, marital status, urban living, diabetes mellitus, hypertension, hypercholesterolemia, chronic kidney disease, total calorie intake, and protein intake. Subjects with anemia had increased ORs for low levels (G2 + G3) of each dimension of EQ-5D compared to subjects without anemia. ORs and 95% CIs for mobility, self-care, and usual activities were 1.208(1.078, 1.353), 1.161(0.98, 1.376), and 1.331(1.173, 1.51), respectively, after adjusting for all covariates. Pain/discomfort and anxiety/depression were not associated with increased ORs for low levels of EQ-5D. CONCLUSIONS: In South Korea, low QoL was associated with anemia, particularly in the mobility, self-care, and usual activities dimensions of EQ-5D. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12889-019-6930-y) contains supplementary material, which is available to authorized users.